(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Background: Autologous blood and steroid injections have been used with different results. Some advocates autologous blood and some favors steroid injection for lateral epicondylitis. Objective: To compare the effects of autologous blood with steroid injection in lateral epicondylitis. Materials and Methods: This study was done at Department of Orthopedics and Trauma Unit, Khyber Teaching Hospital, Peshawar from December 2012 to December 2013. Patients were randomized into 2 groups; autologous blood injection (Group A) and steroid injection (Group B) each comprising of 39 patients to compare the effectiveness of both modalities of improvement in treatment for at least one grade of pain on Visual Analogue Scale at 6 weeks follow up. Data was analyzed by SPSS version10.0. Fisher’s test/ T test was used to compare efficacy keeping p value < 0.05 as significant. Results: In Group A & B, there were 15 (38.46%) and 13 (33.33%) males and 20 (61.54%) and 26 (66.67%) females respectively ((p= 0.8137) and mean ages were 33.61 years + 7.56SD and 33.61 years + 11.65SD respectively ((p=1.0000)). Effectiveness of autologous blood injection and steroid injection was 32 (82.05%) and 20 (21.58%) respectively (p value = 0.0082). Gender (p=1.0000), age (p=0.763) and duration of symptoms (p=0.810) of patients were not significantly affecting the effectiveness. Conclusion: We concluded that autologous blood injection is effective than steroid injection in lateral epicondylitis. Key words: Lateral Epicondylitis, Autologous blood and Steroid injection.